The Effect of Problem Based Learning Model Assisted by PhET Simulation on Understanding Physics Concepts - Rianti, Rianti; Gunawan, Gunawan; Verawati, Ni Nyoman Sri Putu; Taufik, Muhammad (Lensa: Jurnal Kependidikan Fisika, 2024)
This study investigates the impact of the Problem-Based Learning (PBL) model assisted by PhET simulations on students' understanding of physics concepts. Recognizing the persistent challenge students face in grasping abstract physics concepts, this research integrates innovative teaching methods to enhance conceptual comprehension. The study employs a quasi-experimental design with a non-equivalent control group format, involving eleventh-grade science students from SMAN 1 Bayan, North Lombok. The experimental group, taught using the PBL model enhanced with PhET simulations, demonstrated significant improvements in posttest scores compared to the control group, which followed traditional lecture-based instruction. Data analysis, including validity, reliability, discrimination power, and difficulty level tests, confirmed the robustness of the concept understanding instrument. ANOVA results indicated a substantial effect of the intervention, with the experimental group showing a higher mean score and lower variability in performance. The findings reveal that the PBL model, supported by interactive PhET simulations, effectively enhances students' conceptual understanding in physics. This study contributes to the broader discourse on educational innovations by providing empirical evidence of the benefits of combining PBL with technological tools in physics education. It underscores the need for student-centered learning approaches that foster critical thinking and active participation. Future research should explore the scalability of this method across diverse educational contexts and further refine the integration of digital simulations to cover a broader range of physics topics.